Hebo: New Year Ritual of Yem People in South West Ethiopia - Tarekegn, Lemma Nigatu; Terefe, Mandefro Fenta (International journal of multicultural and multireligious understanding, 2019)
Hebo, which is the New Year ritual of Yem, plays a crucial role in resolving conflicts and/or crimes of any kind among the community. The ritual incorporates multistage peacemaking processes. This study describes Hebo ritual performances and reveals peacemaking mechanisms through its stages.  To collect data, participant observation, in-depth interview and document analysis were employed in ethnographic fieldwork. Data were described and interpreted based on the sequences of ritual performances. The findings of the study show that the New Year ritual has multi stage peace maintaining mechanisms that strengthens social cohesion, redirects identity and restores solidarity among the clans. Hence, considering the traditional system of uncovering hidden crimes and peacemaking mechanisms plays significant roles to reinforce peace, social stability and development in the study area in particular and in the country in general.